Fakawel and Coastal Women: A Slice of the Reality of the Relationship between Coastal and Marine Women, and Policy Support in Damuli, Central Halmahera) - Usman, Herman; Can, Laily Ramadhany; Usman, Syarifuddin; Djana, Amrul (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
This study aims to understand the group of women in the Damuli community behind the reality of those who practice fakawel. As a coastal community, the Damuli women's group has a strategy in meeting the needs of daily life. Between women and men there is a division of work that is always maintained so that harmony occurs. The division of work between men and women in Damuli Village, East Patani District, Central Halmahera Regency has existed for a long time, and is well maintained. When the men go to the garden to work, the women go to the coast to find fish (fakawel), complete with the equipment they have. The tradition of fakawel is not only for women fishing alone, but contains the meaning of the relationship between nature and women, where by doing fakawel actually coastal women indirectly take care of the sustainability of coastal environmental ecosystems. The problem is, this tradition has not become a local government policy to improve the standard of living of coastal communities. The method used in this study is a qualitative approach based on the reality that occurs in Damuli society as a result of individual subjective perceptions alone. The paradigm used in this study is interpretive (social action) which explains the phenomenon of women's social roles that are able to construct their social reality.